Analysis of agriculture sustainable development in Russia - Yu. A. Kuzlyakina; V. S. Zamula; O. A. Kuznetsova (Теория и практика переработки мяса)
The article is focused on determining the current situation in Russia on the way to achieving the goals of sustainable development in agriculture. When analyzing the literature, it was revealed that most of the goals and objectives of sustainable development are already, to a greater or lesser degree, incorporated into the main strategic and program documents in Russia. Achievements in the implementation of SDG 2 “End hunger, achieve food security and improved nutrition and promote sustainable agriculture” were considered. Statistical indicators of agriculture sustainable development in Russia are analyzed. The principles for development of the agrifood systems sustainability concept are formulated and presented. In the last century and a half, the main task of Russia in country’s food security has been to feed its population. At the present day, it can be stated that this problem has been mainly solved.